Work Exhaustion in health professionals in Lima metropolitana - Loli Pineda, Alejandro (2008)
The present investigation had as objective to know the level of work exhaustion in health professionals that work in health services of metropolitan area of Lima, in a sample of 89 subjects who were postgraduate students in universities of Lima. The study shows that the work exhaustion in the health professionals is normal with tendency to be still lower. Specifically, we found a negative correlation between stress and the satisfaction with salary, the relation with the patients, the physical environment, and the health state. Also, there was a negative correlation between stress and familiar life, work satisfaction, work schedule, life satisfaction, and enough supplies to work. On the other hand, we found a positive correlation between stress and emotional wearing, depersonalization, and success. Finally, an analysis with the demographic variables indicates to us that it exists association between work satisfaction with sex and type of contract; family life with age, type of contract, and other employ; depersonalisation with academic level; professional accomplishment with working time; affective commitment with antiquity in the institution and monthly net salary; stress with monthly net salary; and economic satisfaction with monthly net salary.